The Impact of the Communicative Behaviour in Social Media on the University Brand Image - Ana Kazaishvili; Lia Khmiadashvili (International School for Social and Business Studies, 2022)
Purpose: Communicative behaviour as a state of relationship which influences bilateral feelings, needs, and thoughts for more unambiguous and open communication (Ivanov & Werner, 2010) can affect the brand image. Correspondingly, communication from the side of the universities toward students through social media has a significant role. Facebook is a powerful communicational channel. It effectively and efficiently took control of the business sector, advertising sector, and furthermore, educational realm. It has an enduring influence on the way how people communicate, and as time passes, it becomes an essential part of their lives. The article presents the behaviours of Georgian higher educational institutions in social media, especially on Facebook, and the attitude of the existing or potential students towards communicative behaviour of HEIs. The findings show what kind of influence does communication in Facebook has on customer perception and correspondingly brand image. Study design/methodology/approach: Considering the sensitivity and nature of the research two types of studies were selected. Observing the behaviour of the universities directly on their Facebook pages was selected as the leading type of the research, since the content, as well as their responsiveness and engagement in further communication, is clearly visible visually. In addition, we have decided to listen to the customers themselves. Because of this reason focus groups of existing and potential students were selected to talk about their expectations and the reality in terms of communicative behaviour of the universities. Findings: The results of both, observation as well as focus group research showed the lacks and lapses of communicative behaviour of Georgian universities on social media, specifically on Facebook. The most crucial ones were detected to be the following: delays in distributing valuable information, content not so much significant and interesting for students, indirect answers to student queries or ignoring at all. Originality/value: Considering the globalizing landscape branding has become crucial for the universities for different reasons. Not only attracting potential students but also for retaining the existing ones and being exceptional they have to follow modern trends. Communication, direct or indirect, being one of the most significant for branding deserves more attention. The value of the current research is showing the expectations of the existing and potential customers and presents the gaps between "what is done" and "what should be done".